ANALISA PENGARUH EARNING POWER DAN ROI TERHADAP HARGA PASAR SAHAM (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2004)
This Research examines the influences of Earning power and Return On Invesment (ROI) upon stockprices in Cement Industry in Surabaya Stock Exchange (SS1Q. It focuses on simultaneous efects of Earning power and ROI towards stock prices. Taking three companies in this industri which has went publicly in Indonesia during six years from 1993 to 1998. Moreover, linear regression model uses in this research to support data analysis. This finding reflects the Earning power and ROI together induce stock prices. However, partially they do not influence the stock prices This may be due to other dominant factors which are giving more uence than that variables used in this research, such as economic crises and unstable US Dollars exchange rate